Dynamics of the Thirteenth-century Depopulation of the Northern San Juan: The View from Cedar Mesa. (1st October 2015) - Matson, R. G.; Lipe, William D.; Curewitz, Diane
Abstract : Tree-ring dates and ceramic seriations are used to refine the chronology of Pueblo depopulation of the Cedar Mesa-Natural Bridges area of southeastern Utah. The early to mid-1200s saw increased occupation in the canyons, but mesa settings continue to be inhabited throughout as well. Wood-cutting for construction tapers off in the 1250s and ends in the 1260s, well before the onset of 1276–1299 "great drought." Factors contributing to the depopulation are reviewed, including regional evidence for shorter growing seasons. Widespread warfare may have motivated people to leave areas of low population density, such as Cedar Mesa, to join the more secure large settlements that continued to grow in southwestern Colorado, even as overall population in that area began to decline.